Nursing students’ perceptions of the qualities of clinical instructors in a public university in Jordan: A qualitative study - Shudifat, Raed; Algunmeeyn, Abdullah; Mahasneh, Deema; Al-Oran, Haytham; Alduraidi, Hamza; Shosha, Ghada Abu (Belitung Raya Foundation, Indonesia, 2024)
Background: Nursing clinical education is a key to developing nursing students’ knowledge, skills, and competencies. Few studies have attempted to explore students’ perceptions regarding the qualities of effective clinical instructors. Objective: The current study aims to explore nursing students’ perceptions of effective clinical instructors’ qualities in Jordan. Methods: A qualitative exploratory approach was used to deepen our understanding of nursing students’ perceptions of effective clinical instructors’ qualities. A total of 21 nursing students were involved, and data were collected from June to August 2023. Data were analyzed using the thematic analysis approach. Results: The thematic analysis revealed two main themes. The first theme was professional qualities, comprising four subthemes: professional knowledge and experience, acting as a role model, performing as a caring one, and assembling effective communication. The second theme was building a good rapport. The findings demonstrated that clinical instructor qualities impacted how students perceived their teaching effectiveness, and they identified professional knowledge and competence as crucial qualities of an effective clinical instructor. It was acknowledged that caring behaviors and effective communication skills were essential behavioral attributes for clinical instructors. Conclusion: Nursing students have valued particular characteristics of effective clinical instructors. These characteristics were knowledge, caring, relationships, role models, and communication. Further research is needed to validate the study’s findings.